(untitled) (Journal of humanities and social sciences exploratio, 2025)
This paper aims to explore the design strategy of public service advertisements in the context of new media and its impact on communication effects. With the popularization of digital technology and mobile Internet, the media, narrative and audience participation methods of public service advertisements have undergone profound changes. This paper first sorts out the relevant theories of visual narrative and communication effect, and then relates to specific cases, and comprehensively analyzes the visual narrative design characteristics of new media public service advertisements from the four perspectives of narrative structure, visual symbols, immersive experience, and interactive design. Research shows that new media public service advertisements break the traditional linear narrative mode through fragmented, scene-based, emotional and gamified design, which can arouse the audience’s emotional resonance and stimulate their willingness to participate, thereby improving the awareness, recognition and secondary communication rate of advertisements. Finally, according to the shortcomings in the current practice, countermeasures and suggestions for visual narrative design and improving communication effects are put forward, hoping to provide some theoretical reference for public welfare communication of other institutions.